Community empowerment in leading pesantren: A research of Nyai’s leadership - Samsu Samsu; Martin Kustati; David D. Perrodin; Mahyudin Ritonga; Muhammad Kosim; Rusmini Rusmini; Suwendi Suwendi (International Journal of Evaluation and Research in Education (IJERE), 2021)
Leadership is one of the essential factors that can influence community involvement in realizing the character of male and female students in the pesantren (Islamic boarding schools) in Jambi, Indonesia. This study proposed Nyai’s (female religious leaders in the pesantren) charismatic, economic, and social responsibility leadership models in the context of community empowerment (CE). This quantitative research aimed to determine the contribution of Nyai’s leadership models to CE. The data from the questionnaire were analyzed using path and flowchart analysis. The results showed that the three Nyai’s leadership models in this study influenced and contributed to CE to support the pesantren’s activities and programs. This study recommended adopting the three Nyai’s leadership models in empowering the community in the pesantren.